(3eNJUQ ZjK GdCOH GdPj GfSLe aj TQM dGejI GdYLes - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s ((3eMeO Hf CHj HcQ eMeO GdNWjH GdSefhOj s)
(3ChdgG (B:s
(3hHYO, aEf GdbUjOI GdehSheI HdGejI GdYLe cGf fGXegG ZGV aj GdHMQ aCJi HOQQ efVhOI s
(3BNQgG (B:s
(3hbGd CHhGdWjH(B: (3hjYQa GdCeQ bHd ehbYg aeG dg HYO acQI fOe s
(3cJH CHjGJ GdbUjOI HGdMeQI hHgG fXGe GdJYbjHI Yf fSNI HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B46 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs